Characteristics of rainfall pattern for crop planning at Jabalpur region (Madhya Pradesh) of India (MAUSAM, 2012)
The daily rainfall data of past 31 years (1978-2008) of Agro meteorological Observatory, Department of Physics & Agriculture Engineering, Jabalpur (Madhya Pradesh) has been analyzed for establishing the long term average of weekly, monthly, seasonal and annual rainfall and its variability. The weekly probability of rainfall was estimated using Markov Chain probability model for receiving >= 10 and 30 mm rainfall per week. The mean annual rainfall observed as 1309 mm and its variability was 27.1 per cent. The highest annual and kharif season rainfall 2083 and 2052 mm respectively were recorded in 1994. On the other hand the lowest annual and kharif rainfall were 620 mm and 471 mm respectively in 1979. The study revealed that the recent decade rainfall has increased during last 31 years. The seasonal average kharif, post monsoon, winter and summer seasons recorded 1197.3 mm, 32.1 mm, 49.8 mm and 29.8 mm of rainfall. About 91.5 per cent of total annual rainfall was received in kharif, 2.5 per cent in post monsoon, 3.8 per cent in winter monsoon and 2.3 per cent in summer. During the period under study 16 per cent of the years recorded excess, 23 per cent deficit and 61 per cent normal rainfall. The July month is regarded as suitable for transplanting of rice crop in Jabalpur region. The highest contribution has been observed in August (33 per cent). Standard week from 25 to 37 received rainfall more than 30 mm indicating the crop growing period from June 2nd week to September last week.